Genetics and genomics of neurobehavioral disorders - Fisch, Gene S. (Totowa, N.J. : Humana Press, 2003)
"Comprehensive and up-to-date, Genetics and Genomics of Neurobehavioral Disorders integrates the molecular, genomic, neuropsychological, and neurobehavioral factors that produce learning disabilities and mental retardation into a coherent framework for the understanding and assessment of neurobehavioral disorders."--Jacket.
The genetics and genomics of neurobehavioral disorders: historical introduction and overview / Gene S. Fisch -- Neuroanatomical considerations specific to the study of neurogenetics / Albert M. Galaburda and J. Eric Schmitt -- Modeling cognitive disorders: from genes to therapies / Rui M. Costa, Ype Elgersma, and Alcino J. Silva -- What can the study of behavioral phenotypes teach us about the pathway from genes to behavior? / Jonathan Flint -- The central nervous system in Neurofibromatosis Type 1 / Nancy Ratner and Kathryn North -- Prader-Willi and Angelman Syndromes: cognitive and behavioral phenotypes / Elisabeth M. Dykens and Suzanne B. Cassidy -- Tuberous Sclerosis / Julian R. Sampson and Julia C. Lewis -- Behavioral phenotype in Velo-Cardio-Facial Syndrome / Kieran C. Murphy -- Williams-Beuren Syndrome / Monica Bayes and Luis A. Perez Jurado -- Behavioral phenotype in Myotonic Dystrophy (Steinert's Disease) / Jean Steyaert -- Genetics of X-Linked Mental Retardation / Jamel Chelly and Ben C.J. Hamel -- Nonsyndromal mental retardation associated with the FRAXE Fragile Site and the FMR2 Gene / Jozef Gecz and Gene S. Fisch -- ATR-X Syndrome / Takahito Wada and Richard J. Gibbons -- The Fragile X Syndrome and the Fragile X mutation / Mark C. Hirst and Gene S. Fisch -- Rett Syndrome: clinical-molecular correlates / Alan K. Percy, Joanna Dragich, and N. Carolyn Schanen.
Includes bibliographical references and index.
Keywords: Neurobehavioral disorders -- Genetic aspects; Electronic books